Intramolecular SEAr reactions of phosphorus compounds: computational approach to the synthesis of π-extended heterocycles - Larrañaga, Olatz; Romero-Nieto, Carlos; Cózar, Abel de (Chemistry - a European journal, 2017)
The reaction mechanism associated with the synthesis of phosphorus-based heteropolyaromatic architectures was investigated by DFT calculations at the B3LYP-D3/6-311+G(D) level of theory. The aim of this study is to provide essential information for the future development of improved polycyclic organophosphorus materials. To that end, the impact of the structure of the initial reactant and/or the intermediates structure on the mechanistic features and energetic profiles of the phosphorus cyclization process was studied. Moreover, the reactivity parameters were analyzed in detail in a conceptual DFT framework and the underlying reactivity trends were extracted. Thus, these findings provide important insights for a rational design of polycyclic phosphorus compounds.
Gesehen am 26.09.2018